A rare variant of carcinoma of the cervix: neuroendocrine tumour - Menon, Maya; TA, Sridevi; A, Satish Selvakumar; RR, Rajeswari (International Journal of Research in Medical Sciences, 2017)
Neuroendocrine neoplasm that occurs in the uterine cervix is rare. It accounts for 0.5-1% of all malignant tumours of the uterine cervix. A 55 years old female patient complained of postmenopausal bleeding and history of foul smelling discharge per vagina since 1 month. On examination cervix appeared bulky, both lips indurated, bleeds on touch, both parametrium involved but not up to pelvic wall with bulky uterus. Vagina and per rectal mucosa was free. Clinical diagnosis of carcinoma cervix, stage 2B was made. Cervix biopsy with HPE revealed squamous epithelium of cervix showing neoplastic cells arranged in nests and prominent perivascular pattern, small round cells with minimal cytoplasm and hyperchromatic nucleus, abundant mitosis, cells showed rosette pattern and isolated foci of cell debris and necrosis. Diagnosis of neuroendocrine tumour of cervix was considered. Immunohistochemistry for cytokeratin, neuron specific enolase, chromogranin and synaptophysin was positive, confirming the final diagnosis of neuroendocrine carcinoma cervix (High grade of small cell type). Recognition of Neuroendocrine carcinoma cervix is important for appropriate therapy & management since these patients have worse clinical outcomes when compared with conventional squamous /adeno carcinoma of cervix. Immunohistochemistry should be supplemented with ultrastructural studies for confirmation and correct categorisation of carcinoma cervix for appropriate management.